Polymorphism of Antifolate Drug Resistance in Plasmodium vivax From Local Residents and Migrant Workers Returned From the China-Myanmar Border - Zeng, Weilin; Wang, Siqi; Feng, Shi; Zhong, Daibin; Hu, Yue; Bai, Yao; Ruan, Yonghua; Si, Yu; Zhao, Hui; Yang, Qi; Li, Xinxin; Chen, Xi; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Drug-resistant Plasmodium vivax malaria impedes efforts to control, eliminate, and ultimately eradicate malaria in Southeast Asia. P. vivax resistance to antifolate drugs derives from point mutations in specific parasite genes, including the dihydropteroate synthase (pvdhps), dihydrofolate reductase (pvdhfr), and GTP cyclohydrolase I (pvgch1) genes. This study aims to investigate the prevalence and spread of drug resistance markers in P. vivax populating the China-Myanmar border. Blood samples were collected from symptomatic patients with acute P. vivax infection. Samples with single-clone P. vivax infections were sequenced for pvdhps and pvdhfr genes and genotyped for 6 flanking microsatellite markers. Copy number variation in the pvgch1 gene was also examined. Polymorphisms were observed in six different codons of the pvdhps gene (382, 383, 512, 549, 553, and 571) and six different codons of the pvdhfr gene (13, 57, 58, 61, 99, 117) in two study sites. The quadruple mutant haplotypes 57I/L/58R/61M/117T of pvdhfr gene were the most common (comprising 76% of cases in Myitsone and 43.7% of case in Laiza). The double mutant haplotype 383G/553G of pvdhps gene was also prevalent at each site (40.8% and 31%). Microsatellites flanking the pvdhfr gene differentiated clinical samples from wild type and quadruple mutant genotypes (FST= 0.259-0.3036), as would be expected for a locus undergoing positive selection. The lack of copy number variation of pvgch1 suggests that SP-resistant P. vivax may harbor alternative mechanisms to secure sufficient folate.